Tea astringency flexible sensor based on bionics and electrochemistry and detection device thereof
Through the flexible tea astringent taste sensor based on bionics and electrochemistry, the problem of insufficient detection limit, speed and accuracy of tea astringent taste is solved, and the rapid and accurate detection of tea astringent taste is achieved, with high detection limit and high accuracy.
Patent Information
- Application Number
- CN202411564630.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art cannot achieve rapid and accurate detection of tea astringent taste, and the detection limit, speed and accuracy are insufficient.
Using a flexible tea astringent taste sensor based on bionics and electrochemistry, the four-step process of preparing interdigit electrodes, preparing pregel solutions, reading ultraviolet polymerized hydrogels and device electrical signals can achieve rapid tea astringent taste Accurate detection.
It realizes a combination of high detection limits, rapid detection and accurate detection of tea astringent taste, and has excellent detection limits, sensitive reaction speed and high accuracy.
Smart Images

Figure CN119438337A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tea astringency detection, in particular to a flexible sensor for tea astringency based on bionics and electrochemistry and a detection device thereof. Background Art
[0002] People are exploring the flavor composition of tea more and more deeply. How to effectively reduce astringency as an important way to improve the taste of tea has attracted much attention. At present, the detection methods of tea astringency have shortcomings such as insufficient detection limit, detection speed and accuracy. The establishment of a fast and accurate method for detecting tea astringency is the main breakthrough direction for improving the taste of tea. At present, there are many related studies on the detection of tea astringency. Some are characterized by fluorescence spectroscopy. For example, the invention patent "A method for evaluating the astringency of tea polyphenols-containing products" (CN202410488450.3) discloses a method for evaluating the astringency of tea polyphenols-containing products. There are also methods for determining the content data of green tea biochemical components and bringing them into the astringency discrimination function to achieve astringency discrimination. For example, the invention patent "A method for discriminating the bitterness of green tea based on the biochemical components of tea" (CN201310571437.6) discloses a method for discriminating the bitterness of green tea based on the biochemical components of tea, which has the advantages of being objective, reliable and quantifiable. The invention patent "A method for analyzing the bitterness intensity of tea leaves" (CN201410416281.9) determines the astringency equivalent concentration intensity of the sample by establishing a correlation function between the signal intensity value of the colloidal electrode and the concentration of the gradient solution of the astringency standard substance. "A method for analyzing the astringency intensity of tea soup" (CN201810766817.8) provides a method for analyzing the astringency intensity of tea soup, which reacts the tea soup sample to be tested with artificial saliva, uses a turbidity meter to analyze its turbidity value, and calculates the astringency intensity of the tea soup through the turbidity value according to the astringency intensity model. Compared with the traditional tea sensory analysis method that relies on reviewers, the test data is more objective and has higher sensitivity and stability, which can avoid human errors of reviewers and achieve objective quantitative analysis of the astringency intensity of tea soup.
[0003] However, the above reports have not been able to achieve the combination of high detection limit, rapid detection and accurate detection for tea astringency detection. This paper will make a flexible interdigital electrode sensor that mimics the saliva layer of the human tongue to achieve rapid and accurate detection of tea astringency. Summary of the invention
[0004] The purpose of the present invention is to fill the gap in the method for rapid and accurate detection of tea astringency, and to provide a flexible sensor for tea astringency based on bionics and electrochemistry and a detection device thereof, so as to solve the problems raised in the above background technology.
[0005] In order to achieve the above-mentioned object, the present invention adopts the following technical scheme: a flexible sensor for tea astringency based on bionics and electrochemistry and a detection device thereof, comprising a four-step process of preparing interdigital electrodes, preparing a pre-gel solution, preparing a UV-polymerized hydrogel and reading the electrical signal of the device;
[0006] The preparation of the interdigital electrode comprises the following steps:
[0007] (1) Selection of substrate film: Choose one of polyethylene terephthalate (PET), polyimide (PI), and polydimethylsiloxane (PDMS). PET / PI / PDMS is widely used in the production of flexible printed circuits.
[0008] (2) Cleaning of the flexible substrate: using anhydrous ethanol to dissolve and remove the oil on the surface of the substrate film, ultrasonically cleaning it in ultrapure water for three times, each time for five minutes, and finally drying it with high-purity nitrogen to obtain a clean substrate film. The cleaned substrate film is placed in a clean and dust-free environment for later use;
[0009] (3) Fabrication of flexible interdigital electrodes: Customize an interdigital electrode mask of the required size, cover the interdigital electrode mask on the flexible substrate, and finally use a gold spraying device to sputter gold. After removing the mask, an electrode model is obtained on the flexible substrate.
[0010] Preferably, the preparation of the pregel solution comprises the following steps:
[0011] (1) Preparation of NaCl solution: Weigh an appropriate amount of sodium chloride and dissolve it in ultrapure water to prepare a 1.5 M NaCl solution;
[0012] (2) Preparation of pregel solution: Dissolve 1-3M acrylamide (AAm) in 1M NaCl solution; then, add 0.5%-1.8% of the weight of acrylamide (AAm) monomer N,N'-methylenebisacrylamide (BIS) to the pregel solution to crosslink the hydrogel, and dissolve it by ultrasonication; after fully dispersing bovine gastric mucin (1-20g / L) in the pregel solution in an ice bath, add 1%-4% of the solution weight of photoinitiator 2,2-diethoxyacetophenone (DEAP), and pass nitrogen gas through the pregel solution for 10 minutes to remove dissolved oxygen.
[0013] Preferably, the UV-polymerized hydrogel comprises the following steps:
[0014] (1) Hydrophilic treatment: The flexible substrate is treated with oxygen plasma for 5-10 minutes, and the hydrophilic treated flexible substrate is placed in a clean and dust-free environment for standby use;
[0015] (2) Silanization treatment: 0.1%-1% solution volume ratio of 3-(trimethoxysilyl)propyl methacrylate (TMSPMA) was added to anhydrous ethanol, and then 0.1%-0.3% acetic acid [10% (acetic acid volume / water volume)] was added and gently stirred to prepare a TMSPMA solution. The flexible substrate was immersed in the TMSPMA solution for 3 minutes to silanize the substrate. After surface functionalization, the substrate was thoroughly washed with ethanol and dried under a nitrogen flow;
[0016] (3) Adding the pregel solution: quickly take the pregel solution to the UV crosslinking instrument, check whether there is precipitation, and drop the pregel solution onto the surface of the interdigital electrode area of the flexible substrate;
[0017] (4) UV cross-linking treatment: The pre-gel solution is polymerized by ultraviolet irradiation, and the polymerized gel is immersed in a NaCl solution of the same concentration overnight to absorb the NaCl solution and reach equilibrium.
[0018] Preferably, the reading of the electrical signal of the device comprises the following steps:
[0019] (1) Insertion or replacement of the sensor: The prepared sensor is inserted or replaced into the device, which contains a small DC resistance tester (range: 2 mΩ to 20 MΩ, current: 10 μA to 100 mA, voltage: 2 V) and a data processing chip, which can convert resistance data into astringency intensity data;
[0020] (2) Wipe or drip sample: wipe the sample (solid) or drip (liquid) on the sensor surface;
[0021] (3) Reading of astringency intensity: After wiping or adding the sample, wait for 10 seconds and the device will display the astringency intensity reading.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] The astringency sensor prepared by the present invention has excellent detection limit, sensitive reaction speed and high accuracy. When the astringent solution diffuses into the hydrogel matrix, the astringent molecules that enter combine with mucin to form hydrophobic molecules, making the porous structure in the hydrogel densified and channelized, enhancing its ion conductivity, and the astringency intensity of the solution can be judged according to the change in sensor resistance.
[0024] Compared with the traditional method, the present invention has better environmental adaptability and portability. Polyethylene terephthalate (PET), polyimide (PI), and polydimethylsiloxane (PDMS) all have good fatigue resistance, heat resistance, and toughness, and are used as flexible substrates in this experiment. After the flexible substrate is treated with oxygen plasma, TMSPMA solution is used as a chemical anchoring agent for silanization. After adding an appropriate amount of pre-gel solution, ultraviolet light polymerizes the hydrogel, and a covalent bond is formed between the hydrogel and the substrate, so that the substrate and the hydrogel are firmly bonded. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the astringency flexible sensor and its detection device of the present invention;
[0026] Figure 2 Schematic diagram of the interdigitated electrode of the present invention.
[0027] In the figure: interdigital electrode-1, base cover-2, digital display screen-3, base-4, flexible substrate layer-11, interdigital electrode layer-12, gel layer-13. DETAILED DESCRIPTION
[0028] In order to further explain the technical solution of the present invention, it is described in detail below through specific embodiments.
[0029] Example 1
[0030] like Figure 1 and Figure 2 As shown, the present invention provides a flexible sensor for tea astringency based on bionics and electrochemistry and a detection device thereof, comprising a four-step process of preparing interdigital electrodes, preparing a pregel solution, UV-polymerizing hydrogel and reading electrical signals of the device.
[0031] Preparation of interdigitated electrodes:
[0032] (1) Polyimide (PI) is selected as the substrate film:
[0033] (2) Cleaning of the PI flexible substrate: Use anhydrous ethanol to dissolve and remove the oil on the surface of the PI film, perform ultrasonic cleaning in ultrapure water for three times, each time for five minutes, and finally blow dry with high-purity nitrogen to obtain a clean PI film. The cleaned PI film is placed in a clean and dust-free environment for later use;
[0034] (3) Fabrication of PI flexible interdigital electrodes: A customized interdigital electrode mask with dimensions of 5 mm*10 mm, line width of 100 um, line spacing of 100 um, and 15 pairs of interdigital pairs was prepared. The interdigital electrode mask was placed on the PI flexible substrate, and gold was finally sputtered using a gold spraying apparatus to obtain a metal layer structure of CU / Ni / AU with thicknesses of 10 um, 4 um, and 2 um, respectively. After removing the mask, an electrode model was obtained on the PI flexible substrate.
[0035] Preparation of pre-gel solution:
[0036] (1) Preparation of NaCl solution: Weigh an appropriate amount of sodium chloride and dissolve it in ultrapure water to prepare a 1.5 M NaCl solution;
[0037] (2) Preparation of pregel solution: 3 M acrylamide (AAm) was dissolved in 1.5 M NaCl solution. Then, 1.5% of the weight of acrylamide (AAm) monomer N,N'-methylenebisacrylamide (BIS) was added to the pregel solution to crosslink the hydrogel. The solution was dissolved by ultrasonication. Bovine gastric mucin (10 g / L) was fully dispersed in the pregel solution in an ice bath. Then, 3% of the solution weight of photoinitiator 2,2-diethoxyacetophenone (DEAP) was added. Nitrogen was passed through the pregel solution for 10 min to remove dissolved oxygen.
[0038] UV-polymerized hydrogels:
[0039] (1) Hydrophilic treatment: The PI flexible substrate is treated with oxygen plasma for 5 min, and the hydrophilic treated PI flexible substrate is placed in a clean and dust-free environment for standby use;
[0040] (2) Silanization treatment: 0.9% solution volume ratio of 3-(trimethoxysilyl)propyl methacrylate (TMSPMA) was added to anhydrous ethanol, and then 0.2% solution volume ratio of acetic acid [10% (acetic acid volume / water volume)] was added and gently stirred to prepare a TMSPMA solution. The PI flexible substrate was immersed in the TMSPMA solution for 5 min to silanize the substrate. After the surface functionalization, the substrate was thoroughly washed with ethanol and dried under a nitrogen flow;
[0041] (3) Adding the pregel solution: quickly take the pregel solution to the UV crosslinking instrument, check whether there is precipitation, and drop the pregel solution onto the surface of the interdigital electrode area of the flexible substrate;
[0042] (4) UV cross-linking treatment: The pre-gel solution was polymerized by irradiating with ultraviolet light (254 nm, 8 W) for 80 min. The polymerized gel was immersed in a NaCl solution of the same concentration overnight to absorb the NaCl solution and reach equilibrium.
[0043] Reading of electrical signals from the device:
[0044] (1) Insertion or replacement of the sensor: The prepared sensor is inserted or replaced into the device, which contains a small DC resistance tester (range: 2 mΩ to 20 MΩ, current: 10 μA to 100 mA, voltage: 2 V) and a data processing chip, which can convert resistance data into astringency intensity data;
[0045] (2) Wipe or drip sample: wipe the sample (solid) or drip (liquid) on the sensor surface;
[0046] (3) Reading of astringency intensity: After wiping or adding the sample, wait for 10 seconds and the device will display the astringency intensity reading.
[0047] Example 2
[0048] Preparation of interdigitated electrodes:
[0049] (1) Polydimethylsiloxane (PDMS) is selected as the substrate film:
[0050] (2) Cleaning of the PDMS flexible substrate: Use anhydrous ethanol to dissolve and remove the oil on the surface of the PDMS film, perform ultrasonic cleaning in ultrapure water for three times, each time for five minutes, and finally blow dry with high-purity nitrogen to obtain a clean PDMS film. The cleaned PDMS film is placed in a clean and dust-free environment for later use;
[0051] (3) Fabrication of PDMS flexible interdigital electrodes: A customized interdigital electrode mask with dimensions of 15 mm*30 mm, line width of 100 um, line spacing of 100 um, and 20 pairs of interdigital pairs was prepared. The interdigital electrode mask was covered on the PDMS flexible substrate, and finally gold was sputtered using a gold spraying apparatus to obtain a metal layer structure of CU / Ni / AU with three layers of thicknesses of 15 um, 4 um, and 1 um, respectively. After removing the mask, an electrode model was obtained on the PDMS flexible substrate.
[0052] Preparation of pre-gel solution:
[0053] (1) Preparation of NaCl solution: Weigh an appropriate amount of sodium chloride and dissolve it in ultrapure water to prepare a 1.5 M NaCl solution;
[0054] (2) Preparation of pregel solution: 2.5 M acrylamide (AAm) was dissolved in 1.5 M NaCl solution. Then, 1.3% of the weight of acrylamide (AAm) monomer N,N'-methylenebisacrylamide (BIS) was added to the pregel solution to crosslink the hydrogel. The solution was dissolved by ultrasonication. Bovine gastric mucin (5 g / L) was fully dispersed in the pregel solution in an ice bath. Then, 2.5% of the solution weight of photoinitiator 2,2-diethoxyacetophenone (DEAP) was added. Nitrogen was passed through the pregel solution for 10 min to remove dissolved oxygen.
[0055] UV-polymerized hydrogels:
[0056] (1) Hydrophilic treatment: The PDMS flexible substrate was treated with oxygen plasma for 5 min, and the hydrophilic treated PDMS flexible substrate was placed in a clean and dust-free environment for standby use;
[0057] (2) Silanization treatment: 0.7% solution volume ratio of 3-(trimethoxysilyl)propyl methacrylate (TMSPMA) was added to anhydrous ethanol, and then 0.25% solution volume ratio of acetic acid [10% (acetic acid volume / water volume)] was added and gently stirred to prepare a TMSPMA solution. The PDMS flexible substrate was immersed in the TMSPMA solution for 3 minutes to silanize the substrate. After the surface functionalization, the substrate was thoroughly washed with ethanol and dried under a nitrogen flow;
[0058] (3) Adding the pregel solution: quickly take the pregel solution to the UV crosslinking instrument, check whether there is precipitation, and drop the pregel solution onto the surface of the interdigital electrode area of the flexible substrate;
[0059] (4) UV cross-linking treatment: The pre-gel solution was polymerized by irradiating ultraviolet light (365 nm, 600 W) for 45 s. The polymerized gel was then immersed in a NaCl solution of the same concentration overnight to absorb the NaCl solution and reach equilibrium.
[0060] Reading of electrical signals from the device:
[0061] (1) Insertion or replacement of the sensor: The prepared sensor is inserted or replaced into the device, which contains a small DC resistance tester (range: 2 mΩ to 20 MΩ, current: 10 μA to 100 mA, voltage: 2 V) and a data processing chip, which can convert resistance data into astringency intensity data;
[0062] (2) Wipe or drip sample: wipe the sample (solid) or drip (liquid) on the sensor surface;
[0063] (3) Reading of astringency intensity: After wiping or adding the sample, wait for 10 seconds and the device will display the astringency intensity reading.
[0064] The above description is only a preferred example of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A flexible sensor for tea astringency based on bionics and electrochemistry and a detection device thereof, characterized in that: The process includes four steps: preparation of interdigitated electrodes, preparation of pre-gel solution, UV polymerization of hydrogel and reading of electrical signals of the device; The preparation of the interdigital electrode comprises the following steps: (1) Selection of substrate film: one of polyethylene terephthalate (PET), polyimide (PI), and polydimethylsiloxane (PDMS); (2) Cleaning of the flexible substrate: using anhydrous ethanol to dissolve and remove the oil on the surface of the substrate film, ultrasonically cleaning it in ultrapure water for three times, each time for five minutes, and finally drying it with high-purity nitrogen to obtain a clean substrate film. The cleaned substrate film is placed in a clean and dust-free environment for later use; (3) Fabrication of flexible interdigital electrodes: Customize an interdigital electrode mask of the required size, cover the interdigital electrode mask on the flexible substrate, and finally use a gold spraying device to sputter gold. After removing the mask, an electrode model is obtained on the flexible substrate.
2. The flexible sensor for tea astringency based on bionics and electrochemistry and its detection device according to claim 1, characterized in that: The preparation of the pre-gel solution comprises the following steps: (1) Preparation of NaCl solution: Weigh an appropriate amount of sodium chloride and dissolve it in ultrapure water to prepare a 1.5 M NaCl solution; (2) Preparation of pregel solution: Dissolve 1-3M acrylamide (AAm) in 1M NaCl solution; then, add 0.5%-1.8% of the weight of acrylamide (AAm) monomer N,N'-methylenebisacrylamide (BIS) to the pregel solution to crosslink the hydrogel, and dissolve it by ultrasonication; after fully dispersing bovine gastric mucin (1-20g / L) in the pregel solution in an ice bath, add 1%-4% of the solution weight of photoinitiator 2,2-diethoxyacetophenone (DEAP), and pass nitrogen gas through the pregel solution for 10 minutes to remove dissolved oxygen.
3. The flexible sensor for tea astringency based on bionics and electrochemistry and its detection device according to claim 1, characterized in that: The UV-polymerized hydrogel comprises the following steps: (1) Hydrophilic treatment: The flexible substrate is treated with oxygen plasma for 5-10 minutes, and the hydrophilic treated flexible substrate is placed in a clean and dust-free environment for standby use; (2) Silanization treatment: 0.1%-1% solution volume ratio of 3-(trimethoxysilyl)propyl methacrylate (TMSPMA) was added to anhydrous ethanol, and then 0.1%-0.3% acetic acid [10% (acetic acid volume / water volume)] was added and gently stirred to prepare a TMSPMA solution. The flexible substrate was immersed in the TMSPMA solution for 3 minutes to silanize the substrate. After surface functionalization, the substrate was thoroughly washed with ethanol and dried under a nitrogen flow; (3) Adding the pregel solution: quickly take the pregel solution to the UV crosslinking instrument, check whether there is precipitation, and drop the pregel solution onto the surface of the interdigital electrode area of the flexible substrate; (4) UV cross-linking treatment: The pre-gel solution is polymerized by ultraviolet irradiation, and the polymerized gel is immersed in a NaCl solution of the same concentration overnight to absorb the NaCl solution and reach equilibrium.
4. The flexible sensor for tea astringency based on bionics and electrochemistry and its detection device according to claim 1, characterized in that: The reading of the electrical signal of the device comprises the following steps: (1) Insertion or replacement of the sensor: The prepared sensor is inserted or replaced into the device, which contains a small DC resistance tester (range: 2 mΩ to 20 MΩ, current: 10 μA to 100 mA, voltage: 2 V) and a data processing chip, which can convert resistance data into astringency intensity data; (2) Wipe or drip sample: wipe the sample (solid) or drip (liquid) on the sensor surface; (3) Reading of astringency intensity: After wiping or adding the sample, wait for 10 seconds and the device will display the astringency intensity reading.
Citation Information
Patent Citations
Bitter and astringent green tea flavors judging method based on tea leaf biochemical components
CN103558311A
A method for analyzing the intensity of bitterness and astringency of tea tree leaves
CN104237335B
Method for analyzing astringency intensity of tea soup
CN109142349A
Method for evaluating astringent taste of tea polyphenol-containing product
CN118329856A